Optic neuritis – general overview with particular emphasis on differential diagnosis - Nowak, Aleksandra; Janus, Anita; Kaptur, Agata; Dziedziński, Dawid; Kwaśniewska, Oliwia; Łoś, Dawid (Quality in Sport, 2024)
Introduction and purpose Optic neuritis (ON), especially retrobulbar, is a common inflammatory neuropathy of the optic nerve occurring typically in young adults. This neuro-ophthalmological condition is involved in the clinical picture of multiple diseases and may be frequently a heralding symptom of them [1,2,3,4,5,7,13]. The main aim of this review is to provide clinicians with thorough information on the possible etiologies of ON, its differentiation and management. Review Methods For this report, we conducted a research of the available, most recent literature in Pubmed and medical books using the keywords (below). As a result, we included over 30 articles and chapters as a benchmark of our analysis. A brief description of the State of Knowledge Optic neuritis is a frequent manifestation of many diseases, with a particular focus on demyelinating processes [1,2,3,4,5,7,13]. Its incidence in central Europe is about 5 per 100 000 people per year [26]. Although the symptoms may be very severe including even abrupt vision loss or intense pain on ocular movement, the prognosis regarding future visual acuity is generally good [1,2,9]. In contrast, the spectrum of diseases underlying optic neuritis is much more diverse [9,10,13,25]. Summary Although a definite diagnosis is not always possible when looking for the cause of ON, it is crucial to know the possible etiologies and to differentiate them as much as we can by means of commonly used tools. In this way, a correct diagnosis will lead to earlier, more personalized treatment and a better overall prognosis [1,5,9,10,11,15,25].